The Influence of Intellectual Intelligence on Primary School Teacher Performance - Syaipudin, Muhammad; Hidayat, Hidayat (General Multidisciplinary Research Journal, 2024)
Introduction: This research aims to investigate the impact of intellectual intelligence on teacher performance in elementary schools. Methods: This research uses 30 surveys as the data collection method. The analytical method in this research is simple linear regression, then for testing the research instrument using product moment for validity testing and Cronbach alpha for reliability testing. Results: The results of the data analysis show that there is a significant relationship between intellectual intelligence and teacher performance. High intellectual intelligence is closely related to improving the quality of teaching and effectiveness in classroom management. Teachers who show a higher level of intellectual intelligence tend to have good adaptability to various learning challenges in elementary schools. Conclusion and suggestion: The implications of these findings can provide a deeper view of the importance of paying attention to aspects of intellectual intelligence in developing human resources in the field of education, especially to improve the quality of teacher performance. This research provides an empirical basis for teacher professional development policies and programs to increase their intellectual intelligence to provide a more optimal contribution to the learning process in elementary schools.